Docking and MM study of non-structural protein (NS5) of Japanese Encephalitis Virus (JEV) with some derivatives of adenosyl - Tiwari, Rakesh Kumar; Pandey, Vinayak; Srivastava, Harshita; Srivastava, Ambrish Kumar; Pandey, Vishnudatt (Frontiers in Chemistry, 2023)
Introduction: The flavivirus NS5, a non-structural protein of Japanese Encephalitis Virus (JEV), a serious deadly human pathogen responsible for epidemics in South East Asia, consists of N-terminal methyl transferase (MTase) domain and RNA-dependent RNA polymerase (RdRp) is known for unique viral genome replication and cap formation activity. S-adenosyl executes a crucial function in these viral activities. S-adenosyl derivatives are chosen as potential binders with the MTase domain of NS5 based on MM and docking studies. Methods: MM GBSA (Generalized Born Surface Area) simulation were performed to evaluate the binding energy, following the 100 nanosecond (ns) production MD simulation in the periodic boundary condition (PBC) for the selected docked ligands with NS5. Quasi-harmonic entropy of the ligands was also calculated with semi-empirical calculations at the PM3/PM6 level supporting docking and MM-GBSA results. Results and discussion: The residue-wise decomposition energy reveals that the key hydrophobic residues Gly 81, Phe 133, and Ile 147 in the RdRp-MTase interface, indicate the biological relevance. These residues act as the key residue stabilizer, binding vigorously with S-Adenosyl derivatives in the vicinity of the interface between the MTase domain and RdRp. This paves the way for the other potential drug as an inhibitor for the enzymatic activity of the NS5.